Transport, Metabolism, and Function of Thyroid Hormones in the Developing Mammalian Brain - Stepien, Barbara K.; Huttner, Wieland B. (Frontiers in Endocrinology, 2019)
Ever since the discovery of thyroid hormone deficiency as the primary cause of cretinism in the second half of the 19th century, the crucial role of thyroid hormone (TH) signaling in embryonic brain development has been established. However, the biological understanding of TH function in brain formation is far from complete, despite advances in treating thyroid function deficiency disorders. The pleiotropic nature of TH action makes it difficult to identify and study discrete roles of TH in various aspect of embryogenesis, including neurogenesis and brain maturation. These challenges notwithstanding, enormous progress has been achieved in understanding TH production and its regulation, their conversions and routes of entry into the developing mammalian brain. The endocrine environment has to adjust when an embryo ceases to rely solely on maternal source of hormones as its own thyroid gland develops and starts to produce endogenous TH. A number of mechanisms are in place to secure the proper delivery and action of TH with placenta, blood-brain interface, and choroid plexus as barriers of entry that need to selectively transport and modify these hormones thus controlling their active levels. Additionally, target cells also possess mechanisms to import, modify and bind TH to further fine-tune their action. A complex picture of a tightly regulated network of transport proteins, modifying enzymes, and receptors has emerged from the past studies. TH have been implicated in multiple processes related to brain formation in mammals—neuronal progenitor proliferation, neuronal migration, functional maturation, and survival—with their exact roles changing over developmental time. Given the plethora of effects thyroid hormones exert on various cell types at different developmental periods, the precise spatiotemporal regulation of their action is of crucial importance. In this review we summarize the current knowledge about TH delivery, conversions, and function in the developing mammalian brain. We also discuss their potential role in vertebrate brain evolution and offer future directions for research aimed at elucidating TH signaling in nervous system development.